2015
DOI: 10.1187/cbe.14-09-0152
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Scientific Communication Skills in Trainees’ Intention to Pursue Biomedical Research Careers: A Social Cognitive Analysis

Abstract: Scientific communication skills are indispensable for success in academic biomedical research careers, but the effort to acquire them can be formidable for trainees and their mentors. The authors investigated whether and how development of these skills affects the academic career intentions of trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 56 publications
2
35
0
Order By: Relevance
“…Career outcome expectations, as well as interests, appear to be much more closely related to choice goals in the Lent model (e.g., take another math course, select engineering as a major), rather than to actual academic performance. Recent data from our group is supportive of this prediction (Cameron et al, 2014). In a structural equation choice model with intention to remain in an academic research career as the choice goal among research trainees, all three cognitive variables (scientific communication self-efficacy, career outcome expectations, and task interest) significantly predicted career intentions.…”
Section: Discussionsupporting
confidence: 64%
“…Career outcome expectations, as well as interests, appear to be much more closely related to choice goals in the Lent model (e.g., take another math course, select engineering as a major), rather than to actual academic performance. Recent data from our group is supportive of this prediction (Cameron et al, 2014). In a structural equation choice model with intention to remain in an academic research career as the choice goal among research trainees, all three cognitive variables (scientific communication self-efficacy, career outcome expectations, and task interest) significantly predicted career intentions.…”
Section: Discussionsupporting
confidence: 64%
“…Increasing familiarity with scientific writing conventions has been reported to improve writing confidence and self-assessed proficiency among doctoral students (29), and an intense, focused delivery of non-discipline-specific writing instruction to graduate students working on theses or dissertations has been shown to improve writing proficiency and research independence as assessed by before-and-after tests (38). Likewise, a study of 510 graduate-level biomedical students in Texas suggests that the development of skills in academic writing can improve research engagement and likelihood of program completion (39). Trainee self-assessments for our workshop indicated that it increased their familiarity with the skills and conventions of biomedical writing as well as their confidence.…”
Section: Discussionmentioning
confidence: 85%
“…Speaking fluently in formal and informal research‐related conversations represents important communication skills that academics/researchers need to acquire early in their training. Despite that importance, no formal education or training on that topic is available in the majority of institutions (Cameron et al., , ). Challenges for fluent professional verbal communication include difficulty in speaking a foreign language, limited professional and general vocabulary, grammatical errors, and anxiety.…”
Section: Benefits Of Wwom On Personal Development Perceived By Particmentioning
confidence: 99%
“…Speaking fluently in formal and informal research-related conversations represents important communication skills that academics/researchers need to acquire early in their training. Despite that importance, no formal education or training on that topic is available in the majority of institutions (Cameron et al, 2013(Cameron et al, , 2015.…”
Section: Other Benefitsmentioning
confidence: 99%